A simple theory of proper names - Korta, Kepa (2015)
In this essay, I address the following question posed by Glezakos (after Kaplan): What determines the form of a namecontaining identity statement? I argue that uses of names are determined by the specific names uttered and the presence (or absence) of coco-referential intentions of the speaker. This explains why utterances of the form a=a are uninformative or knowable a priori, more generally than utterances of the form a=b. My approach has the additional benefit of providing an account of empty names.